LEBAR SAYAP BALOK T DAN BALOK L PADA PORTAL SIMETRIS DUA BENTANG - Syukri Syukri (Portal: Jurnal Teknik Sipil, 2011)
This research conducted to evaluate effective length of L beam and T beam (Lef and Tef) to the length of X direction (Lx) and Y direction (Ly). Model of the structure evaluated was space frame portal by using global coordinate X-Y-Z. Analysis of structure use SAP2000 program version 7.40. The first model of structure is three dimension portal with fix relation between beam and column, monolith relation between beam and plate as shell structure. Result of this analysis taken as benchmark data. The second model of structure is three dimension portal with fix relation for each member (beam and column), T beam and L beam use for replacing the combination of beam-plate. Length of space were equal for Lx and Ly 4 to 10 m (increase step by 1 m). Result of this research obtained effective length of T beam (Tef) = 31,5 cm for Lx = Ly = 4 M, and effective length of L beam (Lef) influenced by Lx and Ly. Keywords: effective length of L beam, three dimension portal, structure analysis.